Identification and Analysis of the Nutrition Value of Black Teripang (Holothuriaedulis) and Sand Teripang (Holothuria Scabra) In the Waitiu Flow of Lewolema District - Tukan, Maria Magdalena N. M.; Betan, Antonius Bao; Bili, Guido Anderlex (International Journal of Natural Science Studies and Development (IJOSS), 2024)
Indonesia is a country with a large area of ​​water, with enormous potential for marine biodiversity which is useful as food, pharmaceuticals and cosmetics. There are several marine biota that produce secondary metabolites that are beneficial to humans, including microorganisms, blue green algae, green algae, brown algae, red algae, sponges, coelenterates, bryozoans, molluscs and sea cucumbers (echinoderms). Sea cucumbers are marine animals classified in the phylum Echinodermata, class Holothuroidea. This animal lives on sandy substrates or can be found in coral ecosystems. Sea cucumbers have complete and quite high nutritional content, but the existence of sea cucumbers with a high population in East Flores Regency has not been utilized properly. This study aims to identify and analyze the nutritional content of Sand Sea Cucumber (Holothuria Scabra) and Black Sea Cucumber (Holothuria Edulis). Identification is based on morphology and body color and spicules of the dorsal integument tissue, while the analysis of nutritional value includes water content and ash content using the gravimetric method, protein content using the Kjeldahl method, fat content using the Soxhlet method and carbohydrate content using the by difference method. The results of the study showed that the nutritional content of Sand Sea Cucumber (Holothuria Scabra) was 5.472% water content, 51.056% ash content, 27.072% protein content, 1.449% fat content and 20.424% carbohydrate content, while the nutritional content of Black Sea Cucumber (Holothuria Edulis) was 6.214% water content, 18.864% ash content, 51.636% protein content, 0.659% fat content and 28.841% carbohydrate content.